Analisis Performance Progressive Web Apps Pada Aplikasi Shopee - Dedi Haryanto; Zulhipni Reno Saputra Elsi (UNIVERSITAS INDO GLOBAL MANDIRI)
Progressive web App is a web-based application development that includes the application of the latest technology from a browser that can be accessed quickly into one application without having to install. Progressive web applications can run like mobile applications in general, and the user interface is like using native applications. Progressive web app was invented in 1990. Progressive web App uses the latest Technology to produce web apps that provide a better User Experience and User Interface than mobile native. Progressive web app that is supported by a system called Service Worker, where the technology provides Offline Functionality, Notifications, Content Updates, Connectivity Changes and others. So that in a slow connection or an unstable connection you can access websites quickly and have the same appearance as the last time you opened the application via a Web Browser. This progressive web app can optimize web app performance to allow users to have an accessible experience with quickly and easily through browsers such as notebooks, personal computers or through mobile devices. This progressive web app is a service worker that allows a web app that can be run through all existing browsers and has a fairly simple and transparent process. So that the page that is opened, on the service worker site which is a proxy client that can be written in javascript, as well as being able to cache the assets needed for offline support which can determine certain events to activate the service worker such as push notifications, camera, and background sync. Keywords : Progressive Web Apps, Web, User Interface, Native Apps, User Experience